The Role of Meaningful Work as a Mediation of Political Organizations on Employee Engagement - Daud, Muh; Siswanti, Dian Novita; Nugraha, Dwi Yan (Jurnal Psikologi Perseptual, 2024)
Employee engagement can generate benefits for the organization and lead to positive work outcomes. However, sometimes the application of organizational politics can affect performance. Thus, meaningful work is needed for employees. The aim of this research is to examine the role of meaningful work mediation on the influence of political organizations on employee engagement. This study used a quantitative method with a cross-sectional survey design. The sample of this research is 317 employees obtained using convenience sampling technique. The scale in this study consists of employee engagement, meaningful work, and political organizations using a five-point Likert model. The results obtained in this study are significant meaningful work mediating the influence of political organizations on employee engagement. This study contributes as reference material in implementing interventions to increase employee engagement in order to gain benefits for the organization.Keterlibatan karyawan dapat menghasilkan manfaat bagi organisasi dan mengarah pada hasil kerja yang positif. Namun, terkadang penerapan politik organisasi dapat mempengaruhi kinerja. Sehingga, diperlukan kebermaknaan kerja bagi para karyawan. Adapun tujuan dalam penelitian yaitu menguji peran mediasi meaningful work pada pengaruh political organizations terhadap employee engagement. Penelitian ini menggunakan metode kuantitatif dengan desain survei cross-sectional. Sampel penelitian ini sebanyak 317 karyawan yang diperoleh menggunakan teknik convenience sampling. Skala dalam penelitian ini terdiri dari skala employee engagement, meaningful work, dan political organizations dengan menggunakan model likert lima point. Hasil yang diperoleh dalam penelitian ini yaitu meaningful work signifikan memediasi pengaruh political organizations terhadap employee engagement. Studi ini berkontribusi sebagai bahan referensi dalam menerapkan intervensi untuk meningkatkan employee engagement guna memperoleh keuntungan bagi organisasi.